Assessment of patient counselling on the common cold treatment at Slovak community pharmacies using mystery shopping - Daniela Mináriková; Tomáš Fazekaš; Peter Minárik; Erika Jurišová (Elsevier, 2019)
Background: Up to now, there have been no data on patient counselling in the Slovak community pharmacies. The literature provides a wide range of activities for which mystery shopping methodology be used, including assessment of patient counselling. Aims and objectives: To assess patient counselling on the common cold treatment with OTC medicine containing zinc provided by Slovak community pharmacists. To analyse this counselling considering the set scenarios, counsellors and their age. Methods: 54 pharmacy students visited 270 different community pharmacies throughout Slovakia in 2 weeks in October 2016 to conduct mystery shopping with set scenarios. For assessment of patient counselling, we defined Counselling Performance. It was conceptualised as weighted mean percentage counselling successes rate of its three categories (Identification, Information and Communication) and their weights. Individual perception of counselling evaluated separately. Student t-test and Person's chi-squared test (p < 0.05) and Cohen delta were used for comparing outcomes and effect size of counselling. A simple linear regression was used to find relationships. Results: The total Counselling Performance was 39.0 ± 22.4%, Identification 30.6 ± 28.7%, Information 39.8 ± 25.1% and Communication 74.3 ± 11.5%. 26.3% pharmacies achieved the average Counselling Performance (41-60%). Subjective Perception had a success rate of 73.4 ± 21.2%, but it could be predicted by the Counselling Performance and the success rate of the three categories only in 1/5 pharmacies. Spontaneous counselling was provided more by pharmacy technicians (p = 0.0009). The duration of counselling was similar when comparing both scenarios, counsellors and their age. The product-requested scenario achieved a higher success rate in the Information category (p = 0.0304; d = 0.27). Pharmacists achieved a higher Counselling Performance (p < 0.0001; d = 0.48) and success rate in categories Identification (p = 0.0001, d = 0.46), Information (p = 0.0004, d = 0.37), and Perception (p = 0.0007; d = 0.54). The estimated age of counsellors did not have any impact on the counselling. Conclusion: Patient counselling on the common cold showed a suboptimal level, particularly considering its content. In the study, we found a significant relationship between the success of counselling and counsellors. Keywords: Patient counselling, Mystery shopping, Counselling performance, Community pharmacy, Common cold